ANALISIS LITERASI KEWIRAUSAHAAN DALAM MENINGKATKAN KEMAMPUAN BISNIS GENERASI MUDA DI KECAMATAN MADIDIR KOTA BITUNG SULAWESI UTARA - Taroreh , Johny; Wuisang, Jerry; Rawung, Stanny; Hormati, Caren M. C. (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2025)
This study aims to determine, describe and analyze, related to the Business Ability of the Young Generation in Madidir District, Bitung City, with the research method, namely Qualitative Description, Number of Informants 5 People, and Data analysis techniques using Observation, interviews and Documentation. Based on the results and discussions above, it can be concluded that the entrepreneurial knowledge obtained by the Young Generation, namely knowledge about the business to be pioneered, knowledge about business management and organization, and knowledge about roles and responsibilities can form an entrepreneurial character in the Young Generation marked by the existence of attitudes and behavior in entrepreneurship. Although after obtaining entrepreneurial literacy, only a small part of the Young Generation has the behavior of an entrepreneur, namely deciding to become an entrepreneur, having real actions in running a business, and having a plan to develop a business. Keywords: Entrepreneurial Literacy, Business Skills, Young generation